The exceptional year of 2022: “deathblow” to glacier summer skiing in the Alps? - Abegg, Bruno; Mayer, Marius (Frontiers in Human Dynamics, 2023)
The summer of 2022 in the European Alps was characterized by extremely warm and dry conditions which led to a record ice melt on Alpine glaciers, also due to the preceding winter season with below average snow cover. Given its dependence on natural conditions, glacier summer skiing was highly affected. We compare the number of glacier ski operating days across the Alps for 2011, 2018 and 2022 and roll forward existing time series data from Austria to include the last three seasons (i.e. 2020 – 2022). Results show considerable decreases in the summer half-year ski operation all over the Alps (-45.1% compared to 2011). Summer ski operation in the meteorological (-63.3%) and astronomical summer (-69.7%) declined even more. In Austria, the decline trend of summer ski operating days continues and reaches all-time lows in 2022. We sum up the impacts of the extreme summer of 2022 on Alpine glacier ski areas and discuss its short- to mid-term repercussions. In combination with demand shifts like the potential change of national ski teams’ training patterns ongoing climate change induced glacier shrinkage might lead to the definite end of Alpine summer skiing in the near future.